Peran Sekolah dalam Menanamkan Nilai Anti-Radikalisme: Studi Kasus di SMA Negeri 72 Jakarta - Najwa Kameela Andjani; Fahroza Ardiyanti Amri; Kartika Aprilia Putri; Riska .; Indah Pridayanti (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2026)
Radicalism and violence in the educational environment are critical issues due to their impact on student development. Schools as formal educational institutions play a strategic role in instilling tolerance, nationalism, and moderation. This article analyzes the school’s role in instilling anti-radicalism values using SMA Negeri 72 Jakarta as a case illustration, especially in the context of a recent incident at the school. This study uses a qualitative descriptive approach through literature review. Data were obtained from academic journals, books, educational policy documents, and news reports related to the school incident. The results indicate that anti-radicalism values can be instilled through integration in learning, extracurricular activities, and inclusive school culture. The incident at SMA Negeri 72 underscores the importance of efforts to shield students from exposure to violence and extremist influences.